Atomically dispersed ruthenium sites on whisker-like secondary microstructure of porous carbon host toward highly efficient hydrogen evolution. Issue 6 (22nd January 2020) - Xing, Liwen; Gao, Hongyi; Hai, Guangtong; Tao, Zhiping; Zhao, Jie; Jia, Dandan; Chen, Xiao; Han, Mengyi; Hong, Song; Zheng, Lirong; Huang, Xiubing; Dong, Wenjun; et al.
Abstract : Atomically dispersed Ru sites on whisker-like secondary microstructure of carbon host are herein demonstrated to significantly improve the intrinsic hydrogen evolution performance for carbon-based materials. Abstract : Owing to the high abundance, good conductivity and excellent tolerance to harsh environment, carbon host materials have recently attracted considerable research interest in the fields of electrochemical hydrogen evolution reaction (HER). However, the deficiency of intrinsic active sites within the carbon host materials substantially gives rise to an inferior HER performance. In this work, atomically dispersed ruthenium active sites are deliberately introduced into the carbon host structure by controlled pyrolysis of Ru-doped ZIF-8. With atomic Ru sites on a unique whisker-like secondary microstructure and a favorable porous texture, the optimal product exhibits a high intrinsic activity as well as robust durability, which especially outperforms the Pt/C benchmarking in alkaline media. A combination of control experiments and theoretical calculations demonstrates that atomically dispersed Ru sites within the carbon host matrix serve as the dominant catalytically active sites, and remarkably optimize the free energy of water molecule dissociation during the Volmer step, thus boosting the HER performance.